The chilean popular rebellion of october 2019: a problematization from Jacques Rancière - Sanhueza Huenupi, Leandro (2020)
The present essay seeks to describe and analyze through the philosophical perspective of Jacques Rancière the so-called social outbreak of October 18, 2019 as a popular and democratic rebellion. First, some key concepts of this philosopher's thought will be developed, such as politics, subjectivation, the people and democracy, as well as some reflections on the concept of post-democracy. Second, through the concept of post-democracy, the Chilean democratic regime will be analyzed, highlighting criticisms and social movements that emerged during the post-dictatorship period. Third, the October process is addressed as the emergence of a new people as well as the repercussions of the Agreement for Peace and the New Political Constitution, a process that is still open today.